Influência das condições hidrodinâmicas nos processos de conversão aeróbia em wetlands construídos de escoamento vertical no tratamento de esgoto doméstico bruto - Jorge Alejandro García Zumalacarregui (2018)
Constructed Wetlands constitutes a system that promotes the wastewater treatment using natural processes. The facility is comprised of a typical first stage of the French system with intermittent feeding, designed and built according to IRSTEA (previously CEMAGREF) recommendations and specifications, with some adaptations. The system, planted with Tifton 85 grass (Cynodon dactylon Pers.), the treatment system consists of three treatment units that operate alternately and in parallel treating raw wastewater of approximately 100 inhabitants (around 1 m2 inhabitant -1 .). In the present research, only two units were evaluated, resulting in approximately 0.6 m 2 inhabitant-1 . Each unit received raw sewage for seven days, alternating feeding each week. The performance of the vertical flow constructed wetlands treating raw domestic wastewater focused on the influence of the hydrodynamic conditions in the pollutants aerobic conversion processes. With a hydraulic application rate of 0.45 m3 m -2 d -1 in the operation unit, the influence of sludge deposit layer accumulation on the system surface, changes in the feeding time and the instantaneous hydraulic loading rate in the hydrodynamic behaviour was evaluated through tests with tracers and adjustments to the mathematical models representing the real outflows. The filter´s ability to transfer oxygen to the liquid was evaluated by means of a non-reactive tracer gas. The influence of changes in the feeding time and the instantaneous hydraulic loading rate considering the analysis and removal of several physical-chemical parameters (temperature, dissolved oxygen, pH , BOD, COD, TSS, TKN and NH4 + -N), was evaluated. The monitoring period was divided into two phases, phase 1, corresponding to the shorter feed time (3 min), feeding through a pump, with higher instantaneous hydraulic loading rate (0.36 m3 m -2 h -1 or 6 0 L m -2 min-1 ) and distribution of the influent using laterals pipes with orifices, and phase 2, characterized by a longer feeding time (8min), feeding by using a dosing siphon, lower instantaneous hydraulic loading rate (0.14 m3 m -2 h -1 or 2.3 L m -2 min-1 ) and distribution using a manifold with laterals with open ends and without orifice. Hydrodynamic tests showed a strong tendency of the flow to the hydraulic system of complete mixing, being detected great dispersion in the units, besides the presence of short circuits and dead zones. Hydrodynamics results tests showed a strong tendency of the flow to the hydraulic of piston flow, being detected the great influence of the surface deposit of layer in the hydrodynamic behavior. In general, the lower feeding time favoured the performance of the system, the mean removal efficiencies for phase 1 and 2 were: COD: 78 and 59%; BOD: 79 and 81%; TSS: 82 and 69%; NTK: 59 and 55% and NH4 + - N: 63 and 54%, respectively. The effluent flow rates were quantified by the volumetric Programa de Pós-graduação em Saneamento, Meio Ambiente e Recursos Hídricos da UFMG iv method. The results of intensive monitoring of the system (daily frequency), studies of solids mass balance and hydraulic behaviour complimented this information. Oxygen transfer rates (OTR) obtained (194 - 230 gO2 m -2 d -1 ) were sufficient to meet VFCW oxygen demand for organic matter degradation and nitrification (96 - 153 gO2 m -2 d -1 ). The results demonstrate that the VFCW-FS design was adequate for Brazilian conditions, leading to capable removal efficiencies for satisfying the effluent discharge requirements in surface water bodies, in Brazil